Economic analysis of microgrids including reliability aspects - Paulo Moisés Costa (2006)
Recently, the new concept of microgrid (mu G) has been emerging on distribution networks as a way to ease the integration of micro generation in LV networks and increase reliability. A mu G is an association of a low voltage distribution network, small modular generation systems (micro-generators), loads and storage devices having some local coordinated functions. This entity can operate in two different modes: interconnected or emergency. In the first mode, the microgrid is connected with the distribution network, importing or exporting electricity and/or ancillary services. When in emergency mode, the microgrid operates isolated from the distribution network and uses local resources, changing from power control to frequency control and, if necessary, shedding load. A micro grid will only be established if its promoters achieve sufficient advantages that justify the incurred costs, namely the investment, operation and maintenance costs. The main purpose of this paper is to identify all the relevant costs and benefits and build a decision model for the situation, taking into account the regulatory framework, which is essential for the definition of some of the benefits. The paper also shows how to include in the evaluation the risk associated to the uncertainties in data and parameters. An illustrative example is included that shows a possible situation of equilibrium between global costs and benefits.